EFFECT OF ELASTIC ANISOTROPY ON TUNNEL WALL DISPLACEMENTS BEHIND A TUNNEL FACE - Tonon F.; Amadei B. (My University, 2002)
The effect of elastic anisotropy (transverse isotropy) on the convergence behind a tunnel face is investigated by means of a parametric study. The applicability of existing expressions for evaluating the convergence behind a tunnel face is also addressed. Two cases are distinguished, according to whether the plane of transverse isotropy strikes parallel to the tunnel axis or not. It is found that the existing expressions (valid for isotropic rock masses under a uniform state of stress) are applicable only when the plane of transverse isotropy strikes parallel to the tunnel axis. When the plane of transverse isotropy does not strike parallel to the tunnel axis, three-dimensional analyses are necessary.